2014
DOI: 10.1136/amiajnl-2013-002605
|View full text |Cite
|
Sign up to set email alerts
|

Availability and quality of mobile health app privacy policies

Abstract: Mobile health (mHealth) customers shopping for applications (apps) should be aware of app privacy practices so they can make informed decisions about purchase and use. We sought to assess the availability, scope, and transparency of mHealth app privacy policies on iOS and Android. Over 35,000 mHealth apps are available for iOS and Android. Of the 600 most commonly used apps, only 183 (30.5%) had privacy policies. Average policy length was 1755 (SD 1301) words with a reading grade level of 16 (SD 2.9). Two thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
229
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(244 citation statements)
references
References 15 publications
13
229
2
Order By: Relevance
“…These findings are consistent with the prior finding by other researchers, who determined that the average grade level of the privacy policy of a mobile health app is grade 16 [8]. As smartphones become more affordable to people of all incomes, the problems posed by complex privacy policies will likely intensify.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings are consistent with the prior finding by other researchers, who determined that the average grade level of the privacy policy of a mobile health app is grade 16 [8]. As smartphones become more affordable to people of all incomes, the problems posed by complex privacy policies will likely intensify.…”
Section: Discussionsupporting
confidence: 90%
“…There were no significant differences in the readability of the privacy policies for apps for diabetes versus mental health. Similar results were found after excluding the common apps (8) from the analysis (data not shown). Overall, the metrics suggest that privacy policies may be difficult for people to read.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…These mobile healthgenerated data are therefore sensitive information and subject of privacy regulations. However, various reports have identified that the majority of mobile apps suffer serious privacy concerns [57,58]. In a recent article, 79 health apps were evaluated for data safety principles.…”
Section: Privacy and Security Of Mobile Appsmentioning
confidence: 99%
“…Moreover, a Weight Watcher's scale was featured in the advertisement in order to maximize effects as extant research (e.g., Pew, 2016;Roeber, Rehse, Knorrek, & Thomsen, 2015;Sunyaev, Dehling, Taylor, & Mandl, 2015) suggests health-related topics elicit greater levels of perceived risk in personalized communication contexts.…”
Section: Designmentioning
confidence: 99%